Photoetching liquid, long-life electroluminescent device and preparation method of long-life electroluminescent device

By using photolithography liquid of modified quantum dots and acrylic modified epoxy resin, combined with the dual curing process of ultraviolet light and thermal curing, the problem of short service life of QLED devices is solved, and a higher curing degree and cross-linking density are achieved, which significantly improves the service life and high temperature resistance of QLED devices.

CN119668026APending Publication Date: 2025-03-21SUZHOU XINGSHUO NANOTECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411425840.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The service life of existing quantum dot light emitting diodes (QLEDs) is relatively short, which affects its application in the field of display technology.

Method used

The photolithography solution with modified quantum dots and acrylic modified epoxy resin is used to improve the curing degree and cross-linking density of the photolithographic nanocrystal layer through the dual curing process of ultraviolet light and thermal curing.

Benefits of technology

It significantly improves the lifetime of QLED devices, reduces volatile components, especially small molecular components, and enhances the high temperature resistance of the photolithographic nanocrystal layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119668026A_ABST
    Figure CN119668026A_ABST
Patent Text Reader

Abstract

The invention provides a photoetching liquid, a long-life photoetching electroluminescent device and a preparation method thereof, and the photoetching liquid comprises modified quantum dots, acrylic acid modified epoxy resin, a photoetching solvent and an initiator; the modified quantum dots comprise quantum dots and modified ligands modified on the surfaces of the quantum dots, and the modified ligands can be in reaction connection with the acrylic acid modified epoxy resin during polymerization reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of electroluminescent devices, and specifically, relates to a photolithography liquid, a long-life electroluminescent device and a preparation method thereof. Background Art

[0002] Quantum dots, also known as semiconductor nanocrystals, are a new type of semiconductor nanomaterial with a size of 1-10nm. Due to the quantum size effect and dielectric confinement effect, they have unique photoluminescence (PL) and electroluminescence (EL) properties. Compared with traditional organic fluorescent dyes, quantum dots have high quantum yield, high photochemical stability, not easy to photolyze, as well as wide excitation, narrow emission, high color purity, and the luminescent color can be adjusted by controlling the size of quantum dots. Excellent optical properties have broad application prospects in the field of display technology.

[0003] Electroluminescent devices based on quantum dots, such as quantum dot light-emitting diodes (QLEDs), have many advantages that LCDs (liquid crystal displays) cannot achieve, such as wide viewing angles, high contrast, fast response speeds, and flexibility. After years of research and development, the maximum external quantum efficiency of QLEDs has been greatly improved, which has met the needs of use; however, in terms of service life, it is not ideal, which has become the main reason that prevents QLEDs from entering actual production applications.

[0004] In view of this, the present application provides a photolithography liquid, a long-life electroluminescent device and a preparation method thereof. The electroluminescent device prepared from the photolithography liquid has a long service life while maintaining excellent electroluminescent performance. Summary of the invention

[0005] The purpose of the present application is to provide a photolithography liquid, a long-life electroluminescent device and a preparation method thereof. The electroluminescent device prepared from the photolithography liquid has a long service life while maintaining excellent electroluminescent performance.

[0006] In a first aspect of the present application, a photolithography liquid is provided, which includes: modified quantum dots, acrylic modified epoxy resin, a photolithography solvent and an initiator; the modified quantum dots include quantum dots and modified ligands modified on the surface of the quantum dots, and the modified ligands can react and connect with the acrylic modified epoxy resin during the polymerization reaction.

[0007] In some embodiments, the modified ligand has a group that can react and attach to an epoxy group.

[0008] Furthermore, the group of the modified ligand capable of reacting and connecting with the epoxy group includes at least one of a thiol group, an amine group, or an acid anhydride.

[0009] Further, the modified ligand includes at least one of pentaerythritol tetrakis (3-mercaptopropionate), pentaerythritol tetrakis (3-mercaptobutyrate), tris [2- (3-mercaptopropionyloxy) ethyl] isocyanurate, 2,3-dimercapto-1-propanol (2-mercaptoacetate), and trimethylolpropane tris (3-mercaptoacetate).

[0010] In some embodiments, the quantum dots are oily quantum dots.

[0011] Further, the quantum dots include at least one of: IIB-VIA group quantum dots, IIIA-VA group quantum dots, IVA-VIA group quantum dots, IVA group quantum dots, IB-IIIA-VIA group quantum dots, IB-IIB-IVA-VIA group quantum dots, VIII-VIA group quantum dots, and perovskite quantum dots. The quantum dots include a core, a shell layer covering the core, and an oily ligand modified on the surface of the shell layer.

[0012] In some embodiments, the acrylic modified epoxy resin contains unsaturated hydrocarbons and epoxy groups.

[0013] Furthermore, the acrylic modified epoxy resin includes at least one of aromatic monoacrylate (CN131NS), modified epoxy acrylate (CN136), monofunctional acrylate (CN152), or epoxy acrylate oligomer (CNUVE150).

[0014] In some embodiments, the photolithography solvent includes at least one of glycol ether, lactate, cellosolve ester, and ketone. Preferably, the photolithography solvent is glycol ether.

[0015] In some embodiments, the initiator includes at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), 2-dimethylamino-2-benzyl-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, methyl benzoylformate, 2,4-dihydroxybenzophenone, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, or 5-nitroacenaphthene.

[0016] A second aspect of the present application provides a method for preparing a photolithography liquid, the preparation method comprising:

[0017] S1, preparing modified quantum dots; the modified quantum dots include quantum dots and modified ligands modified on the surface of the quantum dots, and the modified ligands can react and connect with acrylic modified epoxy resin during polymerization;

[0018] S2, uniformly mixing the modified quantum dots, acrylic modified epoxy resin, photolithography solvent and initiator to form a photolithography solution.

[0019] In some embodiments, quantum dots, a non-polar solvent, and a modified ligand are mixed to form a first mixed solution, and the first mixed solution is reacted to obtain modified quantum dots.

[0020] Further, in the first mixed solution, the mass ratio of the quantum dots to the modified ligand is (1-10): 1. Preferably, in the first mixed solution, the mass ratio of the quantum dots to the modified ligand is (2-5): 1.

[0021] Further, the first mixed solution is reacted for 0.5-10 hours under the protection of an inert gas at a temperature lower than the boiling point of the non-polar solvent to obtain a solution containing the modified ligand, and the non-polar solvent is removed by vacuum drying to obtain the modified ligand. Preferably, the first mixed solution is reacted for 0.5-6 hours under the protection of an inert gas at 55-140°C.

[0022] Furthermore, the non-polar solvent includes at least one of xylene, toluene, trimethylbenzene, chloroform, or tetrahydrofuran.

[0023] In some embodiments, the modified quantum dots, acrylic modified epoxy resin and photolithography solvent are mixed evenly, and then an initiator is added and mixed evenly at a first temperature to form a photolithography solution.

[0024] Furthermore, the modified quantum dots, acrylic modified epoxy resin, initiator and photolithography solvent are added to the photolithography solution in a mass ratio of 100:(8-25):(2-7):(2-8).

[0025] Preferably, in the photolithography solution, the mass ratio of the modified quantum dots, acrylic modified epoxy resin, initiator and photolithography solvent is 100:(10-20):(3-5):(4-6.5).

[0026] Furthermore, the first temperature is 25-80° C., and the mixture is stirred for 0.5-6 hours to be evenly mixed to form a photoresist solution.

[0027] Preferably, the first temperature is 40-70° C., and the stirring time is 0.5-2 hours.

[0028] The third aspect of the present application provides a method for preparing a long-life electroluminescent device, the method comprising: sequentially spin coating a hole injection layer, a hole transport layer, a photolithographic nanocrystal layer, and an electron transport layer on an anode substrate, and evaporating a cathode layer or encapsulating a cathode plate on the electron transport layer to obtain an electroluminescent device; wherein,

[0029] The photolithography nanocrystalline layer is formed by solidifying the photolithography liquid.

[0030] In some embodiments, the photoresist is spin-coated on the hole transport layer, and after exposure and development, the layer is baked at 80-150° C. for 0.3-3 h to obtain a photolithographic nanocrystalline layer.

[0031] The exposure refers to irradiating the spin-coated photoresist under ultraviolet light for 20-60 seconds under the protection of the mask. The development refers to immersing the exposed photoresist in a developer and then washing it with PGMEA for 30-500 seconds.

[0032] The fourth aspect of the present application provides a long-life electroluminescent device obtained by the above-mentioned preparation method.

[0033] Compared with the prior art, the photolithography liquid, long-life electroluminescent device and preparation method thereof of the present application have at least the following advantages:

[0034] (1) The quantum dots of the photolithography liquid of the present application are modified quantum dots. The modified ligands make the quantum dots compatible with other components and, more importantly, have groups that can react and connect with the epoxy groups of the acrylic modified epoxy resin. At the same time, in addition to conventional unsaturated hydrocarbons such as carbon-carbon double bonds, the acrylic modified epoxy resin also has epoxy groups. When preparing QLED devices, after the photolithography liquid is spin-coated, under the irradiation of ultraviolet light (exposure), the unsaturated hydrocarbons of the acrylic modified epoxy resin undergo polymerization and cross-linking and curing (UV curing); after exposure and development, it is dried, and under heating conditions, the modified ligands of the modified quantum dots react and connect with the epoxy groups of the acrylic modified epoxy resin (thermal curing), achieving dual curing (UV curing + thermal curing). The dual curing of the present application makes the photolithography nanocrystal layer have a high degree of curing and a high cross-linking density, and the degree of curing of its UV curing + thermal curing reaches about 98%. Due to the high cross-linking density, the volatile components are small, especially the small molecule components (small molecule components will have a very adverse effect on QLED devices), which can increase the life of QLED devices; at the same time, due to the high cross-linking density, the high temperature resistance of the photolithography nanocrystal layer is improved, further increasing the life of the QLED device.

[0035] (2) The photolithography liquid of the present application only needs to mix the modified quantum dots, acrylic modified epoxy resin, photolithography solvent and initiator, without adding conventional acrylate monomers. When preparing QLED devices (photolithography nanocrystal layer), spin coating, exposure and development can be carried out directly, eliminating the degumming step in the traditional photolithography method. The method is simple and reliable.

[0036] (3) The photolithography liquid of the present application can have quantum dots of various colors to form a full-color QLED device. Compared with the sub-pixel size of tens of microns or larger constructed by current inkjet printing, the present application can easily obtain a high-resolution QLED device with a sub-pixel width as small as sub-micron level, and a long-life QLED device, which is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Combined with the following Figure 1 When read together, the above and other features of the present application will be more fully described. It is understood that these drawings only depict several implementations of the present application and should not be considered as limiting the scope of the present application. By using the drawings, the present application will be more clearly and detailed.

[0038] Figure 1 This is a lighting film surface diagram of the QLED device of Example 1.

[0039] Figure 2 Graph showing the relationship between the brightness and EQE of the QLED device of Example 1.

[0040] Figure 3 This is a film surface image of the QLED device of Example 2 when it is lit.

[0041] Figure 4 This is a graph showing the relationship between the brightness and EQE of the QLED device of Example 2.

[0042] Figure 5 This is a film surface image of the QLED device of Example 3 when it is lit.

[0043] Figure 6 This is a graph showing the relationship between the brightness and EQE of the QLED device of Example 3.

[0044] Figure 7 This is a film surface image of the QLED device of comparative example 1 when it is lit.

[0045] Figure 8 This is a graph showing the relationship between the brightness and EQE of the QLED device of comparative example 1. DETAILED DESCRIPTION

[0046] The following examples are described to assist the understanding of the present application, and the examples are not and should not be interpreted in any way as limiting the scope of protection of the present application.

[0047] If not otherwise defined, all terms (including technical and scientific terms) in this specification may be defined as commonly understood by those skilled in the art to which the present disclosure belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning consistent with their meaning in the context of the present disclosure and the relevant art, and will be interpreted in a non-idealized or overly formal sense unless clearly defined as such in this article.

[0048] As used herein, the term "at least one", when before or after a list of elements, modifies the entire list of elements without modifying the individual elements of the list, and will not be interpreted as limiting "one". "Or" means "and / or". The terms "include" and "comprise", when used in this specification, indicate the presence of the stated features, regions, wholes, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, regions, wholes, steps, operations, elements, components, and / or their collections. Therefore, the above wording will be understood to mean including the stated elements, but not excluding any other elements. The term "and / or" includes any and all combinations of one or more of the associated listed items. The term "multiple" refers to two or more. The term "connection" refers to direct or indirect connection. It will be understood that when an element such as a layer, film, region, or substrate is referred to as "on" another element, it may be directly on the other element or there may also be an intermediate element. On the contrary, when an element is referred to as "directly on" another element, there is no intermediate element. In order to clearly illustrate the embodiments in the figures, some parts that are not actually related to the description may be omitted. The terms "first", "second", "third", etc. may be used herein to describe and distinguish various elements, components, regions, layers and / or parts, but these elements, components, regions, layers and / or parts should not be limited by these terms.

[0049] The photolithography liquid of the present application aims to significantly improve the life of electroluminescent devices (QLED devices). Quantum dots have excellent optical properties such as high photochemical stability, not easy to photolyze, wide excitation, narrow emission, high color purity, and the luminescent color can be adjusted by controlling the size of quantum dots. However, its disadvantage is that quantum dots are not resistant to water and oxygen, nor to high temperatures. Among them, high temperatures will significantly reduce their service life, but QLED devices will continue to release heat when lit, and the heat will accumulate and the temperature will become higher and higher. Therefore, the life of QLED devices in the prior art is generally not long, which seriously affects its application in the field of display technology.

[0050] The applicant has found through research that, in addition to the defects of quantum dots being intolerant to water, oxygen and high temperature, their lifespan is also easily affected by other components. The present application provides a photolithography liquid, in which quantum dots are modified quantum dots. Usually, the prior art also modifies quantum dots, the main purpose of which is to improve the solubility of quantum dots in solvents or other components in the photolithography liquid, thereby increasing the content of quantum dots in the photolithography liquid. The modified quantum dots of the present application, while the modified ligands make the quantum dots compatible with other components, more importantly, have groups that can be reacted and connected with acrylic modified epoxy resins. Specifically, the modified ligands have groups that can be reacted and connected with the epoxy groups of acrylic modified epoxy resins, such as thiol, amine, or anhydride. Acrylic modified epoxy resins are different from conventional monofunctional, difunctional, and trifunctional acrylic resins. Conventional acrylic resins have carbon-carbon double bonds, which can undergo polymerization reactions and cross-linking and curing under the action of initiators, but do not have epoxy groups. The acrylic modified epoxy resins of the present application not only have unsaturated hydrocarbons such as carbon-carbon double bonds, but also have epoxy groups. When preparing QLED devices, after spin coating the photoresist, under the irradiation of ultraviolet light (exposure), the unsaturated hydrocarbons of the acrylic modified epoxy resin undergo polymerization reaction and cross-linking and curing (first curing / UV curing); after exposure and development, it is dried, and under heating conditions, the modified ligands of the modified quantum dots react and connect with the epoxy groups of the acrylic modified epoxy resin (second curing / thermal curing) to achieve dual curing. The dual curing of the present application makes the photolithography nanocrystal layer have a high degree of curing and a high cross-linking density, and its UV curing + thermal curing degree reaches about 98%. 1. Due to the high cross-linking density, its volatile components are small, especially small molecule components. After research, the applicant found that small molecule components will have a very adverse effect on QLED devices. After the small molecule components are reduced, the life of the QLED device can be improved; 2. Due to the high degree of curing and high cross-linking density, the high temperature resistance of the photolithography nanocrystal layer is improved. After testing, its temperature resistance grade is F under the use environment of 155°C, thereby further improving the life of the QLED device.

[0051] In a first aspect of the present application, a photolithography liquid is provided, which includes: modified quantum dots, acrylic modified epoxy resin, a photolithography solvent and an initiator; the modified quantum dots include quantum dots and modified ligands modified on the surface of the quantum dots, and the modified ligands can react and connect with the acrylic modified epoxy resin during the polymerization reaction.

[0052] In some embodiments, the modified ligand has a group that can react and attach to an epoxy group.

[0053] Furthermore, the group of the modified ligand capable of reacting and connecting with the epoxy group includes at least one of a thiol group, an amine group, or an acid anhydride.

[0054] Further, the modified ligand includes at least one of pentaerythritol tetrakis (3-mercaptopropionate), pentaerythritol tetrakis (3-mercaptobutyrate), tris [2- (3-mercaptopropionyloxy) ethyl] isocyanurate, 2,3-dimercapto-1-propanol (2-mercaptoacetate), and trimethylolpropane tris (3-mercaptoacetate).

[0055] In some embodiments, the quantum dots are oily quantum dots. In addition to the hydrophilicity of carbon dots, other quantum dots are usually directly synthesized and have excellent performance. They are oily quantum dots (with organic acids, organic amines, organic phosphine, or thiol on the surface), and water-based quantum dots are formed through additional ligand modification. Therefore, the quantum dots are preferably oily quantum dots.

[0056] Further, the quantum dots include at least one of: IIB-VIA group quantum dots, IIIA-VA group quantum dots, IVA-VIA group quantum dots, IVA group quantum dots, IB-IIIA-VIA group quantum dots, IB-IIB-IVA-VIA group quantum dots, VIII-VIA group quantum dots, and perovskite quantum dots. The quantum dots include a core, a shell layer covering the core, and an oily ligand modified on the surface of the shell layer.

[0057] For example, the core of the IIB-VIA group quantum dots includes: CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, MgSe, MgS, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, MgZnSe, MgZnS, HgZnTeS, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe or a combination thereof. For example, the core of the IIIA-VA group quantum dots includes: GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, InZnP, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb or a combination thereof. For example, the IVA-VIA group quantum dot core includes: SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe or a combination thereof. For example, the IVA group quantum dot core includes: Si, Ge, SiC, SiGe or a combination thereof. For example, the IB-IIIA-VIA group quantum dot core includes: CuInSe2, CuInS2, CuInGaSe, CuInGaS or a combination thereof. For example, the IB-IIB-IVA-VIA group quantum dot core includes: CuZnSnSe, CuZnSnS or a combination thereof. For example, the general structural formula of perovskite quantum dots is one of ABX3, A2B2X6, and A3B3X9, wherein A is a monovalent amine organic cation, a monovalent inorganic metal cation (such as CH3NH3 + 、NH2CHNH2+、C(NH2)3 + , Cs + , Li + 、Na+ , K + , Rb + , aromatic groups, etc.), B is a divalent inorganic metal cation (such as a divalent cation of a rare earth metal, a divalent cation of an alkaline earth metal, a divalent cation of a transition metal, a divalent cation of a post-transition metal, etc.), and X is a monovalent anion (such as a halogen, etc.). In addition to the quantum dots listed, other common quantum dots are also applicable to the present application and are within the scope of protection of the present application. The shell is defined as a material surrounding the core body and may include one or more shells. "Ligand" refers to any molecule or ion that can interact weakly or strongly with a quantum dot (for example, through covalent interactions, ionic interactions, van der Waals interactions, or through interactions with any other molecules on the outer surface of the quantum dot). The oily ligand includes: at least one of an organic acid, an organic amine, an organic phosphine, or a thiol. The organic acid includes: at least one of dodecanoic acid, hexadecanoic acid, octadecanoic acid, oleic acid, undecylenic acid, tetradecylenic acid, stearic acid, or benzoic acid. The organic amine includes: at least one of octylamine, oleylamine, dodecylamine, hexadecylamine, and octadecylamine. The organic phosphine includes at least one of trioctylphosphine, trioctylphosphine oxide, tributylphosphine and diphenylphosphine. The thiol includes at least one of octylmercaptan, dodecanethiol, hexadecanethiol, octadecanethiol and benzylmercaptan.

[0058] In some embodiments, the acrylic modified epoxy resin contains unsaturated hydrocarbons and epoxy groups.

[0059] Furthermore, the acrylic modified epoxy resin includes at least one of aromatic monoacrylate (CN131NS), modified epoxy acrylate (CN136), monofunctional acrylate (CN152), or epoxy acrylate oligomer (CNUVE150).

[0060] The photolithography liquid of the present application has modified quantum dots, and its modified ligands make the quantum dots compatible with other ingredients. More importantly, it has a group that can react and connect with the epoxy group of the acrylic modified epoxy resin. At the same time, in addition to conventional unsaturated hydrocarbons such as carbon-carbon double bonds, the acrylic modified epoxy resin also has an epoxy group. When preparing QLED devices, after the photolithography liquid is spin-coated, under the irradiation of ultraviolet light (exposure), the unsaturated hydrocarbons of the acrylic modified epoxy resin undergo polymerization and cross-linking and curing (UV curing); after exposure and development, it is dried, and under heating conditions, the modified ligands of the modified quantum dots react and connect with the epoxy groups of the acrylic modified epoxy resin (thermal curing), achieving dual curing (UV curing + thermal curing). The dual curing of the present application makes the photolithography nanocrystalline layer have a high degree of curing and a high cross-linking density, and the degree of curing of its UV curing + thermal curing reaches about 98%. Due to the high cross-linking density, the volatile components are small, especially the small molecule components (small molecule components will have a very adverse effect on QLED devices), which can increase the life of QLED devices; at the same time, due to the high cross-linking density, the high temperature resistance of the photolithography nanocrystal layer is improved, further increasing the life of the QLED device.

[0061] In some embodiments, the photolithography solvent includes at least one of glycol ether, lactate, cellosolve ester, and ketone. Preferably, the photolithography solvent is glycol ether.

[0062] The glycol ethers include propylene glycol methyl ether acetate, propylene glycol methyl ether acetate, 2-methoxyethyl ether (diethylene glycol dimethyl ether), ethylene glycol monomethyl ether, propylene glycol monomethyl ether. The lactic acid esters include ethyl lactate or methyl lactate. The cellosolve esters include methyl cellosolve acetate; the ketones include methyl ethyl ketone and cyclohexanone.

[0063] In some embodiments, the initiator includes at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), 2-dimethylamino-2-benzyl-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, methyl benzoylformate, 2,4-dihydroxybenzophenone, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, or 5-nitroacenaphthene.

[0064] A second aspect of the present application provides a method for preparing a photolithography liquid, the preparation method comprising:

[0065] S1, preparing modified quantum dots; the modified quantum dots include quantum dots and modified ligands modified on the surface of the quantum dots, and the modified ligands can react and connect with acrylic modified epoxy resin during polymerization;

[0066] S2, uniformly mixing the modified quantum dots, acrylic modified epoxy resin, photolithography solvent and initiator to form a photolithography solution.

[0067] In some embodiments, quantum dots, a non-polar solvent, and a modified ligand are mixed to form a first mixed solution, and the first mixed solution is reacted to obtain modified quantum dots.

[0068] Further, in the first mixed solution, the mass ratio of the quantum dots to the modified ligand is (1-10): 1. Preferably, in the first mixed solution, the mass ratio of the quantum dots to the modified ligand is (2-5): 1.

[0069] Further, the first mixed solution is reacted for 0.5-10 hours under the protection of an inert gas at a temperature lower than the boiling point of the non-polar solvent to obtain a solution containing the modified ligand, and the non-polar solvent is removed by vacuum drying to obtain the modified ligand. Preferably, the first mixed solution is reacted for 0.5-6 hours under the protection of an inert gas at 55-140°C.

[0070] Furthermore, the non-polar solvent includes at least one of xylene, toluene, trimethylbenzene, chloroform, or tetrahydrofuran.

[0071] In some embodiments, the modified quantum dots, acrylic modified epoxy resin and photolithography solvent are mixed evenly, and then an initiator is added and mixed evenly at a first temperature to form a photolithography solution.

[0072] Furthermore, the modified quantum dots, acrylic modified epoxy resin, initiator and photolithography solvent are added to the photolithography solution in a mass ratio of 100:(8-25):(2-7):(2-8).

[0073] Preferably, in the photolithography solution, the mass ratio of the modified quantum dots, acrylic modified epoxy resin, initiator and photolithography solvent is 100:(10-20):(3-5):(4-6.5).

[0074] Furthermore, the first temperature is 25-80° C., and the mixture is stirred for 0.5-6 hours to be evenly mixed to form a photoresist solution.

[0075] Preferably, the first temperature is 40-70° C., and the stirring time is 0.5-2 hours.

[0076] The photolithography liquid of the present application only needs to mix modified quantum dots, acrylic modified epoxy resin, photolithography solvent and initiator, without adding conventional acrylate monomers. When preparing QLED devices (photolithography nanocrystal layer), spin coating, exposure and development can be carried out directly, eliminating the degumming step in the traditional photolithography method. The method is simple and reliable.

[0077] The third aspect of the present application provides a method for preparing a long-life electroluminescent device, the method comprising: sequentially spin coating a hole injection layer, a hole transport layer, a photolithographic nanocrystal layer, and an electron transport layer on an anode substrate, and evaporating a cathode layer or encapsulating a cathode plate on the electron transport layer to obtain an electroluminescent device; wherein,

[0078] The photolithography nanocrystalline layer is formed by solidifying the photolithography liquid.

[0079] In some embodiments, the photoresist is spin-coated on the hole transport layer, and after exposure and development, the layer is baked at 80-150° C. for 0.3-3 h to obtain a photolithographic nanocrystalline layer.

[0080] The exposure refers to irradiating the spin-coated photoresist under ultraviolet light for 20-60 seconds under the protection of the mask. The development refers to immersing the exposed photoresist in a developer and then washing it with PGMEA for 30-500 seconds.

[0081] In the prior art, the preparation of the photolithography nanocrystal layer also includes the steps of spin coating, exposure, development, and baking. The prior art performs baking to heat and remove the solvent, while in the present application, heating is performed to perform a second curing (thermal curing), that is, under heating conditions, the modified ligands on the modified quantum dots react and connect with the epoxy groups on the acrylic modified epoxy resin, thereby improving the curing degree and cross-linking density of the photolithography nanocrystal layer.

[0082] The fourth aspect of the present application provides a long-life electroluminescent device obtained by the above-mentioned preparation method.

[0083] The present invention will be further described in detail below in conjunction with specific embodiments and comparative examples, but the present invention is not limited to the following embodiments. The implementation conditions used in the embodiments can be further adjusted according to different requirements of specific use, and the unspecified conditions are conventional conditions in the industry.

[0084] Embodiment 1:

[0085] S1, preparation of modified quantum dots:

[0086] 0.25mmol cadmium oxide, 2.5mmol zinc acetate, 1.5mL oleic acid, 0.5mL oleylamine and 5mL 1-octadecene were placed in a 100mL three-necked flask, vacuumed and heated to 120℃ with magnetic stirring for 20min. When the solution became transparent, it was heated to 280℃ under nitrogen protection and kept warm for 20min. Then, 1mL ODE-Se was quickly injected into the solution and reacted for 5min to obtain CdZnSe core solution.

[0087] The solution temperature was quickly raised to 310°C, and 4 ml of zinc oleate solution was added dropwise to the reaction solution within 2 minutes. At the same time, 2.5 ml of TBP-Se was added to the reaction solution at 6 ml / h by a syringe pump. After the addition was completed, the solution was kept at 310°C for 20 minutes to ensure the growth of the ZnSe shell. 3 ml of TBP-S was added to the reaction solution at 10 ml / h by a syringe pump, and the solution was kept warm for 20 minutes. The reaction solution was cooled to 240°C, 0.5 ml of IOT-ODE solution was added, and the solution was kept warm for 10 minutes. The solution was cooled to room temperature to obtain the ZnS shell. The product was precipitated and purified using n-heptane and ethanol, and green light CdZnSe / ZnSe / ZnS quantum dots were finally obtained.

[0088] 100 mg of green light CdZnSe / ZnSe / ZnS quantum dots and 10 mg of pentaerythritol tetrakis (3-mercaptopropionate) were added to 1 ml of xylene, reacted in a nitrogen environment at 80° C. for 60 minutes, and the xylene was removed by vacuum drying to obtain modified quantum dots.

[0089] S2, preparation of photoresist solution:

[0090] Take 100 mg of the above-mentioned modified quantum dots and add them to 5 ml of PGMEA solution. After stirring evenly, add 20 mg of aromatic monoacrylate (Sartomer Asia CN131NS) and 3 mg of TPO, and stir evenly at 60°C in the dark. After centrifugation for 10 minutes, take the supernatant and filter it three times using a 0.22 μm filter head to obtain a photoresist solution.

[0091] S3, preparing QLED devices:

[0092] A 45 nm thick polyethylenedioxythiophene-poly(styrene sulfonate) layer (PEDOT:PSS layer, hole injection layer) and a 40 nm thick poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) layer (TFB, hole transport layer) were sequentially prepared on indium tin oxide glass (anode);

[0093] The above-mentioned photoresist was spin-coated on the TFB layer, and after exposure (under the protection of the mask, irradiated under ultraviolet light for 50 seconds), development (immersed in the developer and then rinsed with PGMEA), baking was carried out at 120° C. for 30 minutes to obtain a photolithography nanocrystalline layer with a thickness of 25 nm;

[0094] A zinc oxide layer (ZnO layer, electron transport layer) with a thickness of 65 nm is prepared by spin coating on the photolithographic nanocrystalline layer; then an Al cathode layer is evaporated on the ZnO layer and packaged to form a green light QLED device (G-QLED).

[0095] The illuminated film surface diagram of the green light QLED device is as follows: Figure 1 As shown, from Figure 1It can be seen that the film surface flatness and uniformity are very good.

[0096] The relationship between the brightness and EQE of the green light QLED device is shown in the figure below: Figure 2 As shown, from Figure 2 It can be seen that as the brightness increases, the external quantum efficiency changes slowly.

[0097] Embodiment 2:

[0098] S1, preparation of modified quantum dots:

[0099] 0.25mmol cadmium oxide, 2.5mmol zinc acetate, 1.5mL oleic acid, 0.5mL oleylamine and 5mL 1-octadecene were placed in a 100mL three-necked flask, vacuumed and heated to 120℃ with magnetic stirring for 20min. When the solution became transparent, it was heated to 280℃ under nitrogen protection and kept warm for 20min. Then, 1mL ODE-Se was quickly injected into the solution and reacted for 5min to obtain CdZnSe core solution.

[0100] The solution temperature was quickly raised to 310°C, and 4 ml of zinc oleate solution was added dropwise to the reaction solution within 2 minutes. At the same time, 2.5 ml of TBP-Se was added to the reaction solution at 6 ml / h by a syringe pump. After the addition was completed, the solution was kept at 310°C for 20 minutes to ensure the growth of the ZnSe shell. 3 ml of TBP-S was added to the reaction solution at 10 ml / h by a syringe pump, and the solution was kept warm for 20 minutes. The reaction solution was cooled to 240°C, 0.5 ml of IOT-ODE solution was added, and the solution was kept warm for 10 minutes. The solution was cooled to room temperature to obtain the ZnS shell. The product was precipitated and purified using n-heptane and ethanol, and green light CdZnSe / ZnSe / ZnS quantum dots were finally obtained.

[0101] 100 mg of green light CdZnSe / ZnSe / ZnS quantum dots and 12 mg of pentaerythritol tetrakis (3-mercaptobutyrate) were added to 1 ml of xylene, reacted in a nitrogen environment at 80° C. for 60 minutes, and the xylene was removed by vacuum drying to obtain modified quantum dots.

[0102] S2, preparation of photoresist solution:

[0103] Take 100 mg of the above-mentioned modified quantum dots and add them to 5 ml of PGMEA solution. After stirring evenly, add 18 mg of modified epoxy acrylate (Sartomer Asia CN136) and 4 mg of TPO, and stir evenly at 60°C in the dark. After centrifugation for 10 minutes, take the supernatant and filter it three times using a 0.22 μm filter head to obtain a photoresist solution.

[0104] S3, preparing QLED devices:

[0105] A 45 nm thick polyethylenedioxythiophene-poly(styrene sulfonate) layer (PEDOT:PSS layer, hole injection layer) and a 40 nm thick poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) layer (TFB, hole transport layer) were sequentially prepared on indium tin oxide glass (anode);

[0106] The above-mentioned photoresist was spin-coated on the TFB layer, and after exposure (under the protection of the mask, irradiated under ultraviolet light for 50 seconds), development (immersed in the developer and then rinsed with PGMEA), baking was performed at 110° C. for 40 minutes to obtain a photolithography nanocrystalline layer with a thickness of 25 nm;

[0107] A zinc oxide layer (ZnO layer, electron transport layer) with a thickness of 65 nm is prepared by spin coating on the photolithographic nanocrystalline layer; then an Al cathode layer is evaporated on the ZnO layer and packaged to form a green light QLED device (G-QLED).

[0108] The illuminated film surface diagram of the green light QLED device is as follows: Figure 3 As shown, from Figure 3 It can be seen that the film surface flatness and uniformity are very good.

[0109] The relationship between the brightness and EQE of the green light QLED device is shown in the figure below: Figure 4 As shown, from Figure 4 It can be seen that as the brightness increases, the external quantum efficiency changes slowly.

[0110] Embodiment 3:

[0111] S1, preparation of modified quantum dots:

[0112] 0.25mmol cadmium oxide, 2.5mmol zinc acetate, 1.5mL oleic acid, 0.5mL oleylamine and 5mL 1-octadecene were placed in a 100mL three-necked flask, vacuumed and heated to 120℃ with magnetic stirring for 20min. When the solution became transparent, it was heated to 280℃ under nitrogen protection and kept warm for 20min. Then, 1mL ODE-Se was quickly injected into the solution and reacted for 5min to obtain CdZnSe core solution.

[0113] The solution temperature was quickly raised to 310°C, and 4 ml of zinc oleate solution was added dropwise to the reaction solution within 2 minutes. At the same time, 2.5 ml of TBP-Se was added to the reaction solution at 6 ml / h by a syringe pump. After the addition was completed, the solution was kept at 310°C for 20 minutes to ensure the growth of the ZnSe shell. 3 ml of TBP-S was added to the reaction solution at 10 ml / h by a syringe pump, and the solution was kept warm for 20 minutes. The reaction solution was cooled to 240°C, 0.5 ml of IOT-ODE solution was added, and the solution was kept warm for 10 minutes. The solution was cooled to room temperature to obtain the ZnS shell. The product was precipitated and purified using n-heptane and ethanol, and green light CdZnSe / ZnSe / ZnS quantum dots were finally obtained.

[0114] 100 mg of green light CdZnSe / ZnSe / ZnS quantum dots and 13 mg of tris[2-(3-mercaptopropionyloxy)ethyl]isocyanurate were added to 2 ml of xylene, reacted in a nitrogen environment at 80° C. for 60 minutes, and the xylene was removed by vacuum drying to obtain modified quantum dots.

[0115] S2, preparation of photoresist solution:

[0116] Take 100 mg of the above-mentioned modified quantum dots and add them to 6 ml of PGMEA solution. After stirring evenly, add 17 mg of epoxy acrylate polymer (Sartomer Asia CNUVE150), add 5 mg of TPO, and stir evenly at 60°C in the dark; after centrifugation for 10 minutes, take the supernatant and filter it repeatedly three times using a 0.22 μm filter head to obtain a photolithography solution.

[0117] S3, preparing QLED devices:

[0118] A 45 nm thick polyethylenedioxythiophene-poly(styrene sulfonate) layer (PEDOT:PSS layer, hole injection layer) and a 40 nm thick poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) layer (TFB, hole transport layer) were sequentially prepared on indium tin oxide glass (anode);

[0119] The above-mentioned photoresist was spin-coated on the TFB layer, and after exposure (under the protection of the mask, irradiated under ultraviolet light for 50 seconds), development (immersed in the developer and then rinsed with PGMEA), baking was performed at 100° C. for 60 minutes to obtain a photolithography nanocrystalline layer with a thickness of 25 nm;

[0120] A zinc oxide layer (ZnO layer, electron transport layer) with a thickness of 65 nm is prepared by spin coating on the photolithographic nanocrystalline layer; then an Al cathode layer is evaporated on the ZnO layer and packaged to form a green light QLED device (G-QLED).

[0121] The illuminated film surface diagram of the green light QLED device is as follows: Figure 5 As shown, from Figure 5 It can be seen that the film surface flatness and uniformity are very good.

[0122] The relationship between the brightness and EQE of the green light QLED device is shown in the figure below: Figure 6 As shown, from Figure 6 It can be seen that as the brightness increases, the external quantum efficiency changes slowly.

[0123] Comparative Example 1:

[0124] S1, preparation of quantum dots:

[0125] 0.25mmol cadmium oxide, 2.5mmol zinc acetate, 1.5mL oleic acid, 0.5mL oleylamine and 5mL 1-octadecene were placed in a 100mL three-necked flask, vacuumed and heated to 120℃ with magnetic stirring for 20min. When the solution became transparent, it was heated to 280℃ under nitrogen protection and kept warm for 20min. Then, 1mL ODE-Se was quickly injected into the solution and reacted for 5min to obtain CdZnSe core solution.

[0126] The solution temperature was quickly raised to 310°C, and 4 ml of zinc oleate solution was added dropwise to the reaction solution within 2 minutes. At the same time, 2.5 ml of TBP-Se was added to the reaction solution at 6 ml / h by a syringe pump. After the addition was completed, the solution was kept at 310°C for 20 minutes to ensure the growth of the ZnSe shell. 3 ml of TBP-S was added to the reaction solution at 10 ml / h by a syringe pump, and the solution was kept warm for 20 minutes. The reaction solution was cooled to 240°C, 0.5 ml of IOT-ODE solution was added, and the solution was kept warm for 10 minutes. The solution was cooled to room temperature to obtain the ZnS shell. The product was precipitated and purified using n-heptane and ethanol, and green light CdZnSe / ZnSe / ZnS quantum dots were finally obtained.

[0127] S2, preparation of photoresist solution:

[0128] Take 100 mg of the above quantum dots and add them to 5 ml of n-octane solution. After stirring evenly, add 15 mg of isobornyl acrylate and 5 mg of tricyclodecane dimethanol diacrylate, add 3 mg of TPO, and stir evenly at 60°C in the dark. After centrifugation for 10 minutes, take the supernatant and filter it three times using a 0.22 μm filter head to obtain a photolithography solution.

[0129] S3, preparing QLED devices:

[0130] A 45 nm thick polyethylenedioxythiophene-poly(styrene sulfonate) layer (PEDOT:PSS layer, hole injection layer) and a 40 nm thick poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) layer (TFB, hole transport layer) were sequentially prepared on indium tin oxide glass (anode);

[0131] The above-mentioned photoresist was spin-coated on the TFB layer, and after exposure (under the protection of the mask, irradiated under ultraviolet light for 50 seconds), development (immersed in the developer and then rinsed with PGMEA), baking was carried out at 120° C. for 30 minutes to obtain a photolithography nanocrystalline layer with a thickness of 25 nm;

[0132] A zinc oxide layer (ZnO layer, electron transport layer) with a thickness of 65 nm is prepared by spin coating on the photolithographic nanocrystalline layer; then an Al cathode layer is evaporated on the ZnO layer and packaged to form a green light QLED device (G-QLED).

[0133] The illuminated film surface diagram of the green light QLED device is as follows: Figure 7 As shown, from Figure 7 It can be seen that the membrane surface is relatively rough and not smooth enough.

[0134] The relationship between the brightness and EQE of the green light QLED device is shown in the figure below: Figure 8 As shown, from Figure 8 It can be seen that with the increase of brightness, the external quantum efficiency decreases significantly and quickly.

[0135] The green light QLED devices prepared in Examples 1-3 and Comparative Example 1 were respectively tested for their lighting voltage, current density at 7V (J@7V), maximum current efficiency (CE@max), maximum external quantum efficiency (EQE@max), maximum brightness at 7V (Lv@max, <7V) and T95 lifespan at 1000nits using a Spectra Scan PR-655 instrument. The test results are shown in Table 1.

[0136] Table 1: Electroluminescent performance test results of embodiments and comparative examples.

[0137]

[0138] As can be seen from Table 1, compared with Comparative Example 1, the maximum current efficiency and maximum external quantum efficiency of the QLED devices in Examples 1-3 are improved, and in particular, the lifespan of the QLED devices is significantly improved.

[0139] Although the present application has disclosed multiple aspects and embodiments, other aspects and embodiments will be obvious to those skilled in the art, and several modifications and improvements may be made without departing from the concept of the present application, all of which belong to the protection scope of the present application. The multiple aspects and embodiments disclosed in the present application are only for illustration and are not intended to limit the present application. The actual protection scope of the present application shall be subject to the claims.

Claims

1. A photolithography liquid, characterized in that: The photolithography liquid comprises: modified quantum dots, acrylic modified epoxy resin, photolithography solvent and initiator; the modified quantum dots comprise quantum dots and modified ligands modified on the surface of the quantum dots, and the modified ligands can react and connect with the acrylic modified epoxy resin during polymerization.

2. The photolithography liquid according to claim 1, characterized in that The modified ligand has a group capable of reacting and connecting with an epoxy group; Preferably, the group of the modified ligand capable of reacting and connecting with the epoxy group comprises at least one of a thiol group, an amine group, or an acid anhydride; Preferably, the modified ligand includes at least one of pentaerythritol tetrakis (3-mercaptopropionate), pentaerythritol tetrakis (3-mercaptobutyrate), tris [2- (3-mercaptopropionyloxy) ethyl] isocyanurate, 2,3-dimercapto-1-propanol (2-mercaptoacetate), and trimethylolpropane tris (3-mercaptoacetate).

3. The photolithography liquid according to claim 1, characterized in that The quantum dots are oily quantum dots; the quantum dots include: at least one of IIB-VIA group quantum dots, IIIA-VA group quantum dots, IVA-VIA group quantum dots, IVA group quantum dots, IB-IIIA-VIA group quantum dots, IB-IIB-IVA-VIA group quantum dots, VIII-VIA group quantum dots, and perovskite quantum dots; the photolithography solvent includes: at least one of glycol ethers, lactates, cellosolve esters, and ketones.

4. The photolithography liquid according to claim 1, characterized in that The acrylic modified epoxy resin contains unsaturated hydrocarbons and epoxy groups; Preferably, the acrylic modified epoxy resin includes at least one of aromatic monoacrylate, modified epoxy acrylate, monofunctional acrylate, or epoxy acrylate oligomer.

5. A method for preparing a photolithographic solution, characterized in that: The preparation method comprises: S1, preparing modified quantum dots; the modified quantum dots include quantum dots and modified ligands modified on the surface of the quantum dots, and the modified ligands can react and connect with acrylic modified epoxy resin during polymerization; S2, uniformly mixing the modified quantum dots, acrylic modified epoxy resin, photolithography solvent and initiator to form a photolithography solution.

6. The method for preparing a photolithographic solution according to claim 5, characterized in that: The quantum dots, the non-polar solvent and the modified ligand are mixed to form a first mixed solution, and the modified quantum dots are obtained by reaction; in the first mixed solution, the quantum dots and the modified ligand are added in a mass ratio of (1-10):

1.

7. The method for preparing a photolithographic solution according to claim 5, characterized in that: The modified quantum dots, acrylic modified epoxy resin and photolithography solvent are mixed evenly, and then an initiator is added, and the mixture is mixed evenly at a first temperature to form a photolithography solution; the modified quantum dots, acrylic modified epoxy resin, initiator and photolithography solvent are added to the photolithography solution in a mass ratio of 100:(8-25):(2-7):(2-8); the first temperature is 25-80° C., and the mixture is stirred for 0.5-6 hours to form a photolithography solution; Preferably, in the photolithography solution, the mass ratio of the modified quantum dots, acrylic modified epoxy resin, initiator and photolithography solvent is 100:(10-20):(3-5):(4-6.5).

8. A method for preparing a long-life electroluminescent device, the method comprising: A hole injection layer, a hole transport layer, a photolithography nanocrystal layer, and an electron transport layer are sequentially spin-coated on an anode substrate, and a cathode layer is evaporated on the electron transport layer or a packaged cathode plate is formed to obtain an electroluminescent device; characterized in that the photolithography nanocrystal layer is solidified from the photolithography liquid as described in any one of claims 1 to 4 or the photolithography liquid obtained by the preparation method as described in any one of claims 5 to 7.

9. The method for preparing a long-life electroluminescent device according to claim 8, characterized in that: The photolithography liquid is spin-coated on the hole transport layer, and after exposure and development, the layer is baked at 80-150° C. for 0.3-3 h to obtain a photolithography nanocrystalline layer.

10. A long-life electroluminescent device, characterized in that: The long-life electroluminescent device is obtained by the preparation method according to any one of claims 8 to 9.